2006
DOI: 10.1016/j.cub.2005.12.032
|View full text |Cite
|
Sign up to set email alerts
|

The Arf6 GEF GEP100/BRAG2 Regulates Cell Adhesion by Controlling Endocytosis of β1 Integrins

Abstract: The small GTPase Arf6 has been shown to regulate the post-endocytic trafficking of a subset of membrane proteins, including beta1 integrins, and inhibition of Arf6 function impairs both cell adhesion and motility. The activity of Arf GTPases is regulated by a large family of guanine nucleotide exchange factors (GEFs). Arf-GEP100/BRAG2 is a GEF with reported specificity for Arf6 in vitro, but it is otherwise poorly characterized. Here we report that BRAG2 exists in two ubiquitously expressed isoforms, which we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
134
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(146 citation statements)
references
References 25 publications
11
134
0
1
Order By: Relevance
“…In addition, silencing of Brag2 also slightly increased a3b1-and a6b1-integrin on the EC surface (data not shown). In line with our results, Dunphy et al [15] demonstrated that silencing of Brag2 in HeLa cells increased surface expression of b1-integrins and cell spreading. Moreover, another study suggested that Brag2 may promote b1-integrin endocytosis [33].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, silencing of Brag2 also slightly increased a3b1-and a6b1-integrin on the EC surface (data not shown). In line with our results, Dunphy et al [15] demonstrated that silencing of Brag2 in HeLa cells increased surface expression of b1-integrins and cell spreading. Moreover, another study suggested that Brag2 may promote b1-integrin endocytosis [33].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, Brag2 was shown to be involved in trafficking processes such as the endocytosis of synaptic AMPA-receptors, E-Cadherin recycling, and phagocytosis of monocytes [21,46,47]. Silencing of Brag2 in HeLa cells increased the surface expression of b1-integrins [15] and a later study indicated that Brag2 might contribute to b1-integrin endocytosis in HeLa cells [33]. However, the role of Brag2 in the regulation of integrins in EC was not studied thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Depletion of BRAG2 in Hela cells results in the accumulation of b1-integrin on the cell surface and a corresponding enhancement of attachment and spreading on fibronectin coated substrates. 18 This effect is selective for b1-integrin, as surface transferrin receptor levels were unaffected. Interestingly, Arf6-depleted cells do not accumulate b1-integrin on the cell surface and actually spread more slowly on fibronectin, in agreement with numerous reports that Arf6 regulates integrin recycling.…”
Section: Integrin Traffickingmentioning
confidence: 96%
“…The use of markers has revealed that these tails exist in live cells, but neither their function nor their regulation is currently understood. Another feature typical of Arf6 activation is the loss of actin stress fibers [27][28][29]. Again, the mechanisms through which this occurs are not well understood, but they are likely to involve crosstalk between Arf6 and Rho family GTPases.…”
Section: Arf Regulation Of Actin Dynamics In the Cell Peripherymentioning
confidence: 99%